Research Progress on the Synergistic Anti-Tumor Effect of Natural Anti-Tumor Components of Chinese Herbal Medicine Combined with Chemotherapy Drugs - Hongrui Zhou; Mengxue Zhang; Huihui Cao; Xintong Du; Xin Zhang; Jin Wang; Xiuli Bi (MDPI AG, 2023)
The application of chemotherapy drugs in tumor treatment has a long history, but the lack of selectivity of drugs often leads to serious side effects during chemotherapy. The natural anti-tumor ingredients derived from Chinese herbal medicine are attracting increased attention due to their diverse anti-tumor effects, abundant resources, and minimal side effects. An effective anti-tumor strategy may lie in the combination of these naturally derived anti-tumor ingredients with conventional chemotherapy drugs. This approach could potentially inhibit tumor growth and the development of drug resistance in tumor cells while reducing the adverse effects of chemotherapy drugs. This review provides a comprehensive overview of the combined therapy strategies integrating natural anti-tumor components from Chinese herbal medicine with chemotherapy drugs in current research. We primarily summarize various compounds in Chinese herbal medicine exhibiting natural anti-tumor activities and the relevant mechanisms in synergistic anti-tumor combination therapy. The focus of this paper is on underlining that this integrative approach, combining natural anti-tumor components of Chinese herbal medicine with chemotherapy drugs, presents a novel cancer treatment methodology, thereby providing new insights for future oncological research.